THE USE OF BABY EINSTEIN VIDEO DISC IN TEACHING VOCABULARY : AN EXSPERIMENTAL STUDY OF THE THIRD GRADE STUDENT AT AN ISLAMIC INTEGRATED EDMENTARY SCHOOL IN GARUT - Sany Yusyfia Maolanie, - (2008)
ABSTRACT The research paper was conducted under the title The Use of Baby Einstein Video Disc in Teaching Vocabulary (An Experimental study of the Third Grade Students at an Islamic Integrated Elementary School in Garut). This study tried to analyze the progress of students' vocabulary building after using Baby Einstein video disc as the new instructional media compared with the students who only used conventional media through printed material. It was also intended to explore 1) whether the use of Baby Einstein video disc is effective in increasing students' English vocabulary in elementary school and 2) how the students response to this program. As the title indicated, this was a quantitative research applying an experimental design. The samples of this research were two classes that consist of 74 students divided into two groups, the experimental and the control groups. The Experimental group was given several treatments in the period of 6 meetings, while the control group was not given any treatments. The research associated to particular data collection strategies, those are pre-test, post-test and questionnaire. Statistical analysis of t-test was used to compute the data obtained. This research reveals that the use of Baby Einstein video disc is effective in increasing the students English vocabulary achievement in the third grade students of elementary school. It was proven by the value of t observed is higher than t critical. It means that there is a significant difference between the mean score obtained by experimental and control groups. So, the null hypothesis applied in this research was rejected. From the questionnaire, the writer has found that nearly all of students (84%) love to learn English using multimedia such as Baby Einstein video disc. And a few of students (16%) don't like to learn English by using this technique.